Upper respiratory tract infection caused by Streptococcus pyogenes: physiopathology and diagnosis (Research, Society and Development, 2020)
Objective: To overview the pathophysiology of infections caused by Streptococcus pyogenes in the upper respiratory tract, their respective complications and how the microbiological diagnosis is performed. Methodology: This study was based on an integrative review of bibliographic research characterized by qualitative approach. The eletronic literature search were using PubMed and ScienceDirect-Elsevier. Articles written in Portuguese, English and Spanish with a search date between 2015 to 2020 were included. The keywords used to search the articles were: Streptococcus pyogenes AND Rheumatic Fever; Streptococcus pyogenes AND Arthritis; Streptococcus pyogenes AND Myocarditis; Streptococcus pyogenes AND Pharyngitis. A total of 2619 articles were found between both databases. 420 in PubMed and 2199 in ScienceDirect databases. At the end of the selection process, 22 articles were chosen to compose the present study. Results: For the spread of the microorganism to occur, it is necessary the interaction of the microorganism with host cells. Depending on characteristics such as pathogenicity, virulence, infectious load and infected region, the probability of invasion can increase considerably and evolve to chronic cases of acute rheumatic fever, post-streptococcal reactive arthritis and rheumatic heart disease. The gold standard for diagnosis is the culture of the oropharynx, however, there are limitations. Diagnosis alternatives are serological tests, such as Anti-streptolysin O (ASLO) and Anti-Deoxyribonuclease B (Anti-DNase B). Conclusion: Depending on the humoral or cellular immune response, the complications of a previous infection caused by S. pyogenes are alarming, since as the contagion evolves and become prominent and irreversible.